Adjusting Insert Thickness and Tibial Slope Do Not Correct Internal Tibial Rotation Loss Caused by PCL Resection: In Vitro Study of a Medial Constraint TKA Implanted with Unrestricted Calipered Kinematic Alignment - Nedopil, Alexander J.; Thadani, Peter J.; McCoy, Thomas H.; Howell, Stephen M.; Hull, Maury L. (The Journal of Knee Surgery, 2021)
Most medial stabilized (MS) total knee arthroplasty (TKA) implants recommend excision of the posterior cruciate ligament (PCL), which eliminates the ligament's tension effect on the tibia that drives tibial rotation and compromises passive internal tibial rotation in flexion. Whether increasing the insert thickness and reducing the posterior tibial slope corrects the loss of rotation without extension loss and undesirable anterior lift-off of the insert is unknown. In 10 fresh-frozen cadaveric knees, an MS design with a medial ball-in-socket (i.e., spherical joint) and lateral flat insert was implanted with unrestricted calipered kinematic alignment (KA) and PCL retention. Trial inserts with goniometric markings measured the internal–external orientation relative to the femoral component's medial condyle at maximum extension and 90 degrees of flexion. After PCL excision, these measurements were repeated with the same insert, a 1 mm thicker insert, and a 2- and 4-mm shim under the posterior tibial baseplate to reduce the tibial slope. Internal tibial rotation from maximum extension and 90 degrees of flexion was 15 degrees with PCL retention and 7 degrees with PCL excision (p < 0.000). With a 1 mm thicker insert, internal rotation was 8 degrees (p < 0.000), and four TKAs lost extension. With a 2 mm shim, internal rotation was 9 degrees (p = 0.001) and two TKAs lost extension. With a 4 mm shim, internal rotation was 10 degrees (p = 0.002) and five TKAs lost extension and three had anterior lift-off. The methods of inserting a 1 mm thicker insert and reducing the posterior slope did not correct the loss of internal tibial rotation after PCL excision and caused extension loss and anterior lift-off in several knees. PCL retention should be considered when using unrestricted calipered KA and implanting a medial ball-in-socket and lateral flat insert TKA design, so the progression of internal tibial rotation and coupled reduction in Q-angle throughout flexion matches the native knee, optimizing the retinacular ligaments' tension and patellofemoral tracking.
Keywords: total knee arthroplasty; calipered; posterior cruciate ligament; tibial rotation; insert thickness